Characterizing and enhancing virus removal by protein A chromatography. Issue 4 (16th January 2019) - Pan, Chinwei; Becerra‐Arteaga, Alejandro; Tran, Benjamin; Chinn, Michael; Wang, Hua; Chen, Qi; Lutz, Herb; Zhang, Min
Abstract: Protein A chromatography is an effective capture step to separate Fc‐containing biopharmaceuticals from cell culture impurities but is generally not effective for virus removal, which tends to vary among different products. Previous findings have pointed to the differences in feedstocks to protein A, composed of the products and other cell culture‐related impurities. To separate the effect of the feedstock components on virus removal, and understand why certain monoclonal antibody (mAb) products have low virus log reduction values (LRVs) across protein A chromatography, we investigated the partitioning of three types of viruses on Eshmuno® A columns. Using pure mAbs, we found that low LRVs were correlated with the presence of the particular mAb product itself, causing altered partitioning patterns. Three virus types were tested, and the trend in partitioning was the same for retrovirus‐like particles (RVLPs) expressed in the cell substrate, and its model virus xenotropic murine leukemia virus (XMuLV), whereas slightly different for murine minute virus. These results were extended from previous observation described by Bach and Connell‐Crowley (2015) studying XMuLV partitioning on MabSelect SuRe columns, providing further evidence using additional types of viruses and resin. Other product‐specific cell culture impurities in harvested cell culture fluid played a lesser role in causing low LRVs. In addition, using high throughput screening (HTS) methods and Eshmuno® A resin plates, we identified excipients with ionic and hydrophobic properties that could potentially alleviate the mAb‐induced LRV reduction, indicating that both ionic and hydrophobic interactions were involved. More excipients of such nature or combinations, once optimized, can potentially be used as load and/or wash additives to improve virus removal by protein A. We have demonstrated that HTS is a valuable tool for this type of screening, whether to gain deeper understanding of a mechanism, or to provide guidance during the optimization of protein A process with improved virus removal. Abstract : Protein A chromatography is an effective capture step to separate Fc‐containing biopharmaceuticals from cell culture impurities but is generally not effective for virus removal, which tends to vary among different products. Previous findings have pointed to the differences in feedstocks to protein A, composed of the products and other cell culture‐related impurities.